Argyreia speciosa (Linn. f.) sweet: A comprehensive review - Galani, V. J.; Patel, B. G.; Patel, N. B. (Pharmacognosy Reviews)
Argyreia speciosa (Linn. f.) Sweet is a popular Indian medicinal plant, which has long been used in traditional Ayurvedic Indian medicine for various diseases. This plant is pharmacologically studied for nootropic, aphrodisiac, immunomodulatory, hepatoprotective, antioxidant, antiinflammatory, antihyperglycemic, antidiarrheal, antimicrobial, antiviral, nematicidal, antiulcer, anticonvulsant, analgesic and central nervous depressant activities. A wide range of phytochemical constituents have been isolated from this plant. A comprehensive account of the morphology, phytochemical constituents and pharmacological activities reported are included in view of the many recent findings of importance on this plant.
Keywords: Anticonvulsant activity; antioxidant activity; Argyreia speciosa; central nervous depressant activity; immunomodulatory activity